Oxide Copper Nanoparticles Stabilized by Acrylonitrile and Methyl Methacrylate Polar Monomers Through a Ligand Exchange Reaction - Ramírez-Pastén, S; Ramírez-Pastén, S (IOP Publishing Ltd, 2021)
This research reports the synthesis of copper oxide nanoparticles (CuONP) functionalized by the polar monomers acrylonitrile (ACN) and methyl methacrylate (MMA). The synthesis was achieved by a practical exchange ligand reaction from CuONP previously stabilized by hexadecyltrimethylammonium bromide (CTAB). The replacement of CTAB by ACN or MMA produced the functionalized nanoparticles CuONP-ACN and CuONP-MMA, respectively. The functionalized nanoparticles were characterized by ultraviolet-visible spectroscopy (UV-vis), Fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (SEM), dynamic light scattering (DLS), Zeta potential, x-ray diffraction (XRD), high-resolution-transmission electron microscopy (HR-TEM), and selected area electron diffraction (SAED) analysis. Changes in surface plasmon resonance (SPR) band and the functional group bands observed in UV-vis and FTIR spectra confirmed the efficient replacement of CTAB by polar monomers. Moreover, CuONP-ACN and CuONP-MMA showed a negative surface charge with spherical morphology. X-ray diffraction (XRD) analysis showed that a monoclinic CuO crystal system was formed. © 2021 The Author(s). Published by IOP Publishing Ltd.